Effects of 3‐ and 5‐Year Treatment With Risedronate on Bone Mineralization Density Distribution in Triple Biopsies of the Iliac Crest in Postmenopausal Women - Zoehrer, Ruth; Roschger, Paul; Paschalis, Eleftherios P; Hofstaetter, Jochen G; Durchschlag, Erich; Fratzl, Peter; Phipps, Roger; Klaushofer, Klaus (Journal of bone and mineral research, 2006)
Long‐term effects of risedronate on bone mineralization density distribution in triple transiliac crest biopsies of osteoporotic women were evaluated. In this double‐blinded study, 3‐ and 5‐year treatment with risedronate increased the degree and homogeneity of mineralization without producing hypermineralization. These changes at the material level of bone could contribute to risedronate's antifracture efficacy. Introduction: Risedronate, a nitrogen‐containing bisphosphonate, is widely used in the treatment of osteoporosis. It reduces bone turnover, increases BMD, and decreases fracture risk. To date, there are no data available on the long‐term effects of risedronate on bone mineralization density distribution (BMDD) in humans. Materials and Methods: Osteoporotic women enrolled in the VERT‐NA trial received either risedronate (5 mg/day, orally) or placebo for up to 5 years. All subjects received calcium and vitamin D supplementation if deficient at baseline. Triple iliac crest biopsies were collected from a subset of these subjects at baseline and 3 and 5 years. BMDD was measured in these biopsies using quantitative backscattered electron imaging, and the data were also compared with a normal reference group. Results: At baseline, both risedronate and placebo groups had a lower degree and a greater heterogeneity of mineralization as well as an increase in low mineralized bone compared with the normal reference group. The degree of mineralization increased significantly in the risedronate as well as in the placebo group after 3‐ and 5‐year treatment compared with baseline. However, the degree of mineralization did not exceed that of normal. Three‐year treatment with risedronate significantly increased the homogeneity of mineralization and slightly decreased low mineralized bone compared with placebo. Surprisingly with 5‐year risedronate treatment, heterogeneity of mineralization increased compared with 3‐year treatment, which might indicate an increase in newly formed bone. Conclusions: Long‐term treatment with risedronate affects the homogeneity and degree of mineralization without inducing hypermineralization of the bone matrix. These changes at the material level of the bone matrix may contribute to risedronate's antifracture efficacy in osteoporotic patients.